DRIP FERTIGATION REGIME FOR POTATO ON SANDY SOIL - Feng, zhiwen; Wan, shuqin; Kang, yaohu; Liu, shiping (Emirates Journal of Food and Agriculture, 2017)
To establish the optimum fertilizer rate and propose an appropriate drip fertigation regime for potato (Solanum tuberosum L.) on sandy soil, a two-year field experiment comparing different fertigation levels on potato yield, irrigation water productivity (IWP) and partial fertilizer productivity (PFP) was carried out during 2012–2013. The treatments included five fertigation levels: 10%, 30%, 50%, 70% and 90% of the recommended fertilizer dose of 420:105:495 of N:P:K in kg ha–1 year–1 in 2012; and 10%, 35%, 60%, 85% and 110% of the recommended dose of 390:150:465 of N:P:K in kg ha–1 year–1 in 2013. The recommended fertilizer dose was estimated based on the method of nutrient balance for a target yield of 45.0 Mg ha–1. The soil matric potential at 20 cm depth beneath the emitters was controlled above –25 kPa for drip fertigation. Results showed the highest tuber yield was 38.0 Mg ha–1 for 90%NPK in 2012 and 45.8 Mg ha–1 for 60%NPK in 2013, which was significantly higher than that for 10%NPK. The highest IWP was for 70%NPK in 2012 and 60%NPK in 2013. The highest PFP values were 255.5 kg kg−1 in 2012 and 316.4 kg kg−1 in 2013, recorded in the 10%NPK plots and were significantly higher than for other fertigation treatments. High yield levels of potatoes and both high IWP and PFP could be reached by drip fertigation with 72% of the recommended fertilization dose. Compared with the recommended fertilizer dose, the yield and IWP of 72% NPK increased by 5.9% and 4.7%, respectively. It was possible to make average savings in one season alone of 136, 36 and 152 kg ha–1 N, P2O5 and K2O, respectively. In conclusion, drip fertigation with 72% NPK should be considered optimum for potato production on sandy soils. Each fertilizer amount based on irrigation interval was applied with irrigation quota at 5–6 mm when soil matric potential at soil depths of 20 cm immediately under drip emitters reached –25 kPa. Furthermore, drip fertigation was triggered when 10 consecutive days were without fertigation or rainfall in 24 h exceeded 10 mm.